Gangguan Pemrosesan Bahasa Akibat Trauma Emosional pada Tokoh Tari dalam Film Bolehkah Sekali Saja Aku Menangis - Bariah Bariah; Dhea Azkia Shalehah; Muhammad Sugianor; Nazwa Ramadhani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
Language processing disorders are disorders that arise when someone is under mental stress or experiencing deep emotional trauma. This study aims to analyze the various types of language processing disorders experienced by the character Tari in the film "Bolehkah Sekali Saja Aku Menangis" (May I Cry Once) and to determine the relationship between the character's emotional state and the linguistic symptoms that appear. This study uses a qualitative approach with a naturalistic approach and analytical descriptive methods, where data are collected through observation and recording of dialogues in the film that show signs of language disorders. Samples were taken purposively based on statements that indicate irregularities in sentence structure, long pauses, repetitions, or inappropriate word choices. This analysis compares the results of the study with existing psycholinguistic theories regarding how language processing works and the influence of trauma on speech production. The findings of this study indicate four main types of language processing disorders experienced by the character Tari: unfinished sentences, long pauses, repetitions of words or phrases, and inaccuracies in word choice. These types of disorders are more apparent when the character experiences high emotional stress and when interacting with family members related to her trauma. The results of this study support the theory that emotional trauma can disrupt verbal working memory function and speech planning processes, ultimately impeding communication skills.